Interjurisdictional coordination capacities of cultural policies: contributions from a case study to the analysis of public policies for culture in contemporary Argentina - Morán, Franco (Revista Extraprensa, 2021)
The following paper reflects on cultural public policies, particularly those aimed at the performing arts, as a way of exemplifying and pointing out the importance of the coordination between state spheres for a more effective execution of such policies. We consider that coordination between government levels is a means of achieving policies that provide a comprehensive response to the problems emerging in the field of culture and should be analyzed in greater detail to clarify its key role, not only in implementation, but also in the design of future policies. The Provincial Theater Festival of the province of Córdoba, organized by the Instituto Nacional del Teatro (National Theater Institute – INT), the main executing agency of public policies for the performing arts in Argentina, will be observed as an example. Thus, the administrative and political capacities of the INT will be analyzed to understand possible ways of developing a synergy among the various actors, which will contribute to overcome the mere sum of the parts, and instead incorporate actions that allow managing increasingly integrated and comprehensive responses.